A new species of Lucasioides Kwon (Isopoda: Oniscidea: Agnaridae) from China - Li, Weichun (Zootaxa, 2017)
Lucasioides nudus sp. n. is described from Jiangxi Province, China. The new species can be diagnosed by the cephalon having a well-developed median lobe, the pereonite 1 with acutely postero-lateral corners and sinuous posterior margin of epimeron, the male pleopod 1 endopod without setules, and the bilobed exopod with the outer lobe much shorter and broader than the acute triangular inner lobe.